Prevalence and determinants of malnutrition in children under five in rural Bareilly, India - Sarswat, Gauri; Katyal, Rashmi; Agarwal , Medhavi (International Journal Of Community Medicine And Public Health, 2025)
Background: Malnutrition remains a significant public health concern, especially in low-resource settings. This cross-sectional study investigates the prevalence and socio-demographic determinants of malnutrition among children under five years of age in Rural areas of Bareilly district. To assess the prevalence of malnutrition and identify its socio-demographic determinants among under five children in rural Bareilly, using WHO anthropometric indicators. Methods: The study was conducted in rural areas of Bareilly under the Family Adoption Program initiated by Rohilkhand Medical College and Hospital. Data was collected over a six-month period from rural areas of Bareilly. Results: Based on WHO Z-scores, the prevalence of wasting, underweight and stunting was 12.3%, 26% and 36.6%, respectively. These findings are consistent with the National Family Health Survey (NFHS-5) and underscore the urgent need for multi-sectoral interventions to combat both acute and chronic forms of malnutrition in vulnerable populations. Conclusions: The results align with national and regional trends, reinforcing the need for comprehensive, community-based strategies to address childhood malnutrition.